PENGARUH SOLVABILITAS, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Otes Suriana; Fraternesi Fraternesi; Erwin Febriansyah (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2020)
Company value is the price that prospective buyers are willing to pay if the company is sold. Company value is defined as market value. Because the value of the company can provide maximum prosperity for shareholders if the company's stock price increases. The higher the stock price, the higher the shareholder prosperity. This study aims to find out how much influence solvency, profitability, and liquidity have on firm value. The data used in this study are secondary data obtained from the financial statements of manufacturing companies listed on the Stock Exchange in the 2016-2018 period. The sampling technique used was purposive sampling. The number of companies sampled in this study were 35 companies so that the total sample of the study was 105 observations. The data analysis method used is multiple linear regression analysis. The results of this study are still many variables outside the study that can explain the value of the company. The coefficient of determination is 0.495, which means 49.5% of the company's value is influenced by these variables, while the rest is explained by other variables. Based on the results it can be concluded that solvency, profitability, and liquidity have a significant effect on firm valueKeywords: Solvency, Profitability, Liquidity, and Firm ValueÂ